KOMPETENSI AUDITOR SYARIAH MODEL KSOC DITINJAU DARI PERSPEKTIF ISLAM - Luluk Musfiroh; Dwi Suhartini; Lina Dwi Mayasari (BAJ: Behavioral Accounting Journal, 2021)
This study aims to analyze the competence of the KSOC model of sharia auditors from an Islamic perspective. The research method used is qualitative research, namely library research. The type of library research used is the study of revelatory texts. The researcher collected Al-Quran verses and hadiths regarding the competency elements of the KSOC model of sharia auditors (knowledge, skills and other characteristics). The results showed that Islam illustrates that the three elements of the KSOC are interrelated with one another. Science in the view of Islam is related to faith. The two of them cannot be separated to obtain a high position before Allah SWT. Faith and knowledge that are constantly honed and applied in carrying out tasks will create skills and expertise. Faith also creates integrity, works hard, a willingness to always learn and develop oneself continuously. When the three of them are put together, it will create a professional sharia auditor.